2021
DOI: 10.3390/s21248297
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Preferences of Using Ambient Sensor-Based Lifelogging Technologies in Home Environments

Abstract: Diverse sensor-based technologies can be used to track (older and frail) people’s movements and behaviors in order to detect anomalies and emergencies. Using several ambient sensors and integrating them into an assisting ambient system allows for the early identification of emergency situations and health-related changes. Typical examples are passive infrared sensors (PIR), humidity and temperature sensors (H&T) as well as magnetic sensors (MAG). So far, it is not known whether and to what extent these thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The first research question (RQ1) of this study referred to the general perception and acceptance of video-based AAL technology. In line with previous research, the results of this study confirmed that video-based AAL technologies are evaluated on a neutral, slightly rejecting level, indicating that visual approaches are perceived to be more critical than audio or rather binary technologies [ 13 , 14 ], such as room presence sensors, heat sensors, or humidity sensors [ 65 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The first research question (RQ1) of this study referred to the general perception and acceptance of video-based AAL technology. In line with previous research, the results of this study confirmed that video-based AAL technologies are evaluated on a neutral, slightly rejecting level, indicating that visual approaches are perceived to be more critical than audio or rather binary technologies [ 13 , 14 ], such as room presence sensors, heat sensors, or humidity sensors [ 65 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the perceived benefits, the results of this study revealed high confirming evaluations of perceived barriers as well, in particular regarding privacy-related aspects, whereas the economic and technical concerns were comparably low. These high confirmations of the (privacy-related) perceived barriers are characteristic of video-based AAL technologies, as previous research clearly identified lower evaluations of these barriers and concerns related to AAL technologies in general [ 14 ] or in specific, such as sensor-based AAL systems [ 65 ]. The high relevance of privacy-related concerns already suggests that communication and information strategies should focus on privacy handling and data security when video-based AAL technologies are implemented.…”
Section: Discussionmentioning
confidence: 61%
“…Lifelogs are real-world data of daily lives recorded and stored on personal devices, portable storage systems, or in the cloud. Lifelogging involves a series of procedures that collect and process data through sensors and smart devices [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. A personal health record is considered a dataset consisting of an individual’s lifelog as well as a hospital’s clinical data.…”
Section: Introductionmentioning
confidence: 99%